Editorial: Reflecting in the shade of pandemic - Bulent Tarman (Research in Social Sciences and Technology- OpenED Network, 2020)
I hope this editorial note finds you well and healthy, especially amid the uncertainty due to COVID-19. We are concerned about our children, families, neighbors, colleagues, and ourselves. We are contending with daily reports of death presented as the centerpiece headline news while we are dealing with grief and uncertainty. The impact of this current pandemic on society, in general, is increasingly visible, and we find ourselves in a permanent state of transformation due to the dizzying proliferation of technologies. This pandemic expedites the vital role of Information and Communication Technology (ICT) that drives the modern world in education as well as in all other areas. On the other hand, as schools and higher education institutions rapidly move their learning, teaching, and assessment online in response to the worldwide pandemic, academics feel improvised, inefficiently supported, and deeply fearful.